2012
DOI: 10.1063/1.3702819
|View full text |Cite
|
Sign up to set email alerts
|

Tunable terahertz optical antennas based on graphene ring structures

Abstract: Highly tunable optical antennas in teraherz range based on graphene ring structures are proposed, which employ graphene plasmons instead of traditional metallic plasmons. The plasmon resonances of the perfect graphene ring (PGR) can be understood with the edge plasmons in graphene ribbons. While in the nonconcentric graphene ring, the multipolar plasmon modes appear and anti-symmetric mode splits due to symmetry breaking. Furthermore, the symmetric plasmon mode in a graphene ring can concentrate electromagneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(55 citation statements)
references
References 23 publications
0
55
0
Order By: Relevance
“…The dielectric layer D2 not only supports the graphene and metal strips, but also provides space for destructive interference as the case in metamaterial absorbers. 13 On the other hand, the top dielectric layer is for protecting the graphene and metal strips as well as providing extra degree of freedom for impedance matching so to shift the working frequency to lower band. To verify the effect of D1 on the absorbing screen's bandwidth, simulated results are displayed in Fig.…”
Section: Shift Of Frequency Bands and Influence Of Incident Anglesmentioning
confidence: 99%
See 2 more Smart Citations
“…The dielectric layer D2 not only supports the graphene and metal strips, but also provides space for destructive interference as the case in metamaterial absorbers. 13 On the other hand, the top dielectric layer is for protecting the graphene and metal strips as well as providing extra degree of freedom for impedance matching so to shift the working frequency to lower band. To verify the effect of D1 on the absorbing screen's bandwidth, simulated results are displayed in Fig.…”
Section: Shift Of Frequency Bands and Influence Of Incident Anglesmentioning
confidence: 99%
“…10,11 The applications of graphene also cover wide frequency ranging from optical frequency to THz, [5][6][7][12][13][14][15][16][17] infrared to microwave band. [18][19][20] Among these works, tunable cloaks, 12 polarizers and metasurface are designed with help of electrically tunability of graphene sheet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, these modes are sensitivie to electrostatic doping of graphene, making them highly attractive for electrical control of light on the nanometer scale. For these reasons, the interest in GPs is steadily increasing in theoretical and experimental communities [10,11].Different amazing physical phenomena involving GPs have already been studied, including waveguiding [9,[12][13][14], strong light-matter interaction [15][16][17] and enhanced light absorption [18][19][20]. Recent experimental studies of both propagating and cavity-like graphene plasmons have confirmed their extremely short wavelengths (i.e.…”
mentioning
confidence: 99%
“…In recent years, THz techniques have been used to study the electric states in graphene [25][26][27][28][29][30]. Given the ultra-high carrier mobility of graphene, it also has applications in THz optoelectronics such as transformation optics [23], tunable THz modulators [31][32][33][34][35], room-temperature THz detectors [36], THz optical antennas [37], etc. These graphene-based THz devices have important applications, such as in medical diagnostics, molecular biology, and homeland security.…”
mentioning
confidence: 99%